O estudo do monitoramento dos impactos pós-implantação do aterro sanitário de Uberlândia/MG - Borges, Karoline (2016)
The objectives of this work were to study the practices of monitoring post-implantation environmental impacts, to analyze how these practices have been taking place in Uberlândia Landfill (AS-UDIA) and to propose improvements in this monitoring. Two methodological processes were used: first it was constituted of bibliographical research; And the second was a case study applied to AS-UDIA, comprising documentary research, field research with impact assessment, and the application of a questionnaire for residents, an area surrounding the landfill. Through the bibliographical research were listed 32 potential impacts caused by the implantation and operation of sanitary landfills and respective aspects / parameters of monitoring. Of these impacts identified in the literature, only 22 are present in the EIA of AS-UDIA enlargement and 19 are monitored periodically. Among the unmonitored impacts are: water body quality after receiving the treated manure, diseases transmitted by vectors in the surrounding region and cumulative impacts such as odor and dust in the region near the landfill. After the application of questionnaires, it was found that there are signs of property devaluation in the area under study, as well as other impacts pointed out by the community, such as the decharacterization of the landscape, dust and offensive odors from the operation of the project. After identifying the environmental impacts, most of the community claims the desire to change neighborhoods. Therefore, it is necessary to improve the monitoring of the post-implantation EIA of the AS-UDIA, through the implementation of social programs for the purpose of socio-environmental integration with surrounding population and execution of monitoring of the impacts not foreseen in the EIA or listed, but not Accompanied.